Consolidation vs. Enlargement — the issue for the European community - Hajo Hasenpflug (Intereconomics, 1977)
The EC Council of Ministers seems to have made up its mind to admit Greece to the Community. If so, the accession of the other South European countries willing to join — Spain, Portugal and Turkey — is merely a question of time. What are the implications of such an enlargement of the EC for the Community of the Nine and for the four new members?
Keywords: 330; Integration